Routledge handbook of NATO - Olsen, John Andreas 1968- (Routledge, Taylor & Francis Group, 2024)
"This handbook provides a comprehensive survey of the development and importance of the North Atlantic Treaty Organisation, its role in international relations and its influence on history. The volume examines the Alliance's evolution in breadth, depth and context by analysing and explaining why and how NATO has endured and remained relevant since its creation. To present an inclusive study of the Alliance's activities and milestone events and to offer a glimpse of future challenges, the book's twenty-nine chapters fall into six thematic sections that act as frameworks and allow the exploration of specific topics that pertain to the evolution of NATO: Part I: History of NATO, 1949-2024. Part II: Key Enduring Themes, 1949-2024. Part III: Military Operations, 1995-2024 Part IV: National Perspectives, 1949-2024. Part V: Regional Perspectives, 1949-2024. Part VI: Future Prospects, 2024. This handbook will be of much interest to students and researchers of NATO, strategic studies, defence studies and International Relations, as well as for staff and fellows at security- and defence-oriented think tanks and government officials, military personnel and other practitioners in the areas of foreign affairs and defence."
Keywords: NATO; Geschichte; North Atlantic Treaty Organization / Handbooks, manuals, etc; North Atlantic Treaty Organization / History